1987
DOI: 10.1123/tsp.1.1.4
|View full text |Cite
|
Sign up to set email alerts
|

The Sport Psychology Consultant: Analysis of Critical Components as Viewed by Canadian Olympic Athletes

Abstract: Intensive interviews were conducted with each of 75 Canadian Olympic athletes representing 19 different sports in order to evaluate the sport psychology services offered to them. Athletes representing 12 of the sports indicated they had worked with 1 of 11 sport psychology consultants in preparation for the 1984 Olympic Games. Some were highly satisfied with their consultant and his or her mental training program, others were highly dissatisfied. A profile of the best and worst consultants was developed based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(56 citation statements)
references
References 1 publication
3
48
0
2
Order By: Relevance
“…They also acknowledged the problems of reflective practice when conducted alone: that the practitioner is limited by their own self-knowledge and does not have the resource of another trusted, well-intentioned and skilled practitioner to offer challenge and support. Petitpas et al (1999) outlined the importance of self-awareness in the practitioner-athlete relationship in successful sport psychology delivery, supported by previous research (Danish, 1985;Orlick & Partington, 1987). They advocated the importance of self-knowledge and the examination of many of the assumptions that practitioners hold about themselves and the world.…”
Section: The Importance Of Self-awarenessmentioning
confidence: 73%
“…They also acknowledged the problems of reflective practice when conducted alone: that the practitioner is limited by their own self-knowledge and does not have the resource of another trusted, well-intentioned and skilled practitioner to offer challenge and support. Petitpas et al (1999) outlined the importance of self-awareness in the practitioner-athlete relationship in successful sport psychology delivery, supported by previous research (Danish, 1985;Orlick & Partington, 1987). They advocated the importance of self-knowledge and the examination of many of the assumptions that practitioners hold about themselves and the world.…”
Section: The Importance Of Self-awarenessmentioning
confidence: 73%
“…The participants suggested that getting this balance between intervening and being in the background is not PREPARING ATHLETES AND TEAMS FOR THE OLYMPICS 28 always straightforward, and does develop with experience. It is important for neophyte practitioners to learn this lesson, since athletes and coaches have suggested that the best sport psychology consultants are knowledgeable enough to meet an individual's needs, yet can implement interventions in an applied and flexible manner, identifying when support is necessary (Orlick & Partington, 1987;Statler, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…Within the introduction, the researcher explained the purpose of the investigation, the format of the interview and how the results might be used. The questions contained within the protocol were based upon those used by Orlick and Partington (1987) to evaluate consultant services and covered four general areas: (1) knowledge and awareness of sport psychology (e.g. When did you first hear about the use of sport psychology within soccer?…”
Section: Interview Schedulementioning
confidence: 99%